2021
DOI: 10.1155/2021/3456542
|View full text |Cite
|
Sign up to set email alerts
|

Chlorogenic Acid Alleviates Colon Mucosal Damage Induced by a High‐Fat Diet via Gut Microflora Adjustment to Increase Short‐Chain Fatty Acid Accumulation in Rats

Abstract: A high-fat diet (HFD) has been previously associated with the development of diseases such as chronic colitis. While chlorogenic acid (CGA) is known to exhibit potent antioxidant, antibacterial, and anti-inflammatory properties, little is known about its effects on intestinal inflammation. In this study, we investigated the effects of CGA on intestinal inflammation in an HFD-induced obesity rat model and assessed whether these effects were related to changes in gut microbiota composition. This was achieved by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 51 publications
2
21
1
Order By: Relevance
“…Conversely, oral butyrate could alleviate DSS-induced colitis in mice ( Wang R. X. et al, 2020 ). In addition, another previous study has demonstrated that supplementation of CGA could increase the production of butyric acid subsequently to alleviate HFD-induced intestinal inflammation in rats ( Xie et al, 2021 ). In parallel, dietary CGA supplementation increased butyric acid concentration in the colon, which means that CGA supplementation could improve the gut health of weaned pigs ( Zhang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 98%
“…Conversely, oral butyrate could alleviate DSS-induced colitis in mice ( Wang R. X. et al, 2020 ). In addition, another previous study has demonstrated that supplementation of CGA could increase the production of butyric acid subsequently to alleviate HFD-induced intestinal inflammation in rats ( Xie et al, 2021 ). In parallel, dietary CGA supplementation increased butyric acid concentration in the colon, which means that CGA supplementation could improve the gut health of weaned pigs ( Zhang et al, 2018 ).…”
Section: Discussionmentioning
confidence: 98%
“…However, there are few studies on the effect of CGA on gut microbiota, intestinal mucosal barrier, short-chain fatty acids and GLP-1 in NAFLD patients or animal models. Xie M found CGA can alleviate colitis in HFD-induced obesity through its anti-inflammatory effects associated with changes in gut microbiota composition and an increase in the production of short-chain fatty acids ( Xie et al, 2021 ). Mccarty MF found that CGA could increase GLP-1 secretion, thereby reducing the risk of diabetes ( Mccarty, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…At phylum level, the relative abundance of Firmicutes with respect to Bacteroidetes (F/B ratio) was decreased among all the FRJ groups. Since an increment of F/B ratio was related to an imbalance in the taxonomic composition of gut microbiota [ 37 ], eventually resulting in metabolic disorders [ 38 ], it indicated that the FRJ might promote a healthier state of microbial composition. This hypothesis was supported by facts that all the FRJ doses improved the SCFAs production and the gene expression of ZO-1, Claudin-1, Claudin-4, Ocdudin, E-cadherin, and Muc-2 in mice, which were positively correlated to the intestinal barrier function [ 19 ].…”
Section: Discussionmentioning
confidence: 99%